Maximizing the potential and outreach of Department of Community Medicine and School of Public Health in COVID 19 - Goel, Sonu; Upadhyay, Kritika; Singh, Amarjeet (Indian Journal of Community Health, 2021)
Teaching and learning has existence from the earliest times of human civilization. Socrates in 300 BC involved his learners by dialectic method which has inspired philosophers for more than two thousand years. The argumentative dialogue based on oral questioning and answering process to stimulate critical thinking in the dialectic method allowed others to learn by self-generated deeper understanding.(1) The Gurukul teaching in the ancient vedic time encourages the students to stay in guru’s place (termed as Gurukul) where the education was delivered through scriptures describing vedas, rules of sacrifice, understanding secrets of nature and correlating them with their real life. In these times, the education was more organized and disciplined focusing upon memory retention and concentration(2). The learning through script and writing started in 3500BC where Egyptians developed alphabets from hieroglyphs prototype which was used either on stone monuments or on papyrus, a flexible paper like material.(3)The script was later adopted by Greeks (Phoenician writing system)(4) in 11th century and thereafter by China in 1400-2100BC (oracle bone script)